Authority of the state police of the republic of Indonesia in conducting supervision, security and action against foreigners in Indonesia - Aris Wahjudi,; Made Warka,; Hufron,; Sri Setiadji, (Technium Social Sciences Journal, 2024)
Globalization supported by advances in transformation technology has encouraged the mobility of the world's population to visit other countries in turn. In the destination country, these people are known as foreigners. The mobility of these foreigners is motivated by various reasons, such as business, research, tourism, study, and various other reasons. Indonesia is one of the countries involved in the global chessboard, of course it must be ready for the various consequences that arise, especially related to the entry and exit of foreigners in the territory of Indonesia. The authority of the Police in supervising, securing, and taking action against foreigners in Indonesia has fluctuated between being present and non-existent, resulting in legal uncertainty regarding involvement the Police. Theoretically, the regulation of authority the Police in supervising, securing, and taking action against foreigners in Indonesia, there is a dissynchronization between the 2011 Immigration Law and the 1945 Constitution of Republic Indonesia and its implementing regulations, as well as disharmony between the 2011 Immigration Law and the Police Law, and the Criminal Procedure Code, so that in its implementation it results in apathy or passivity in supervising, securing, and taking action against foreigners in Indonesia.